1987
DOI: 10.1080/01635588709513908
|View full text |Cite
|
Sign up to set email alerts
|

Case‐control study of dietary etiological factors: The Melbourne colorectal cancer study

Abstract: As part of a large-scale investigation of colorectal cancer (CRC) incidence, etiology, and survival, a case-control study was conducted to identify dietary factors associated with the risk of CRC. The study compared 715 cases with 727 age- and sex-matched community controls. A quantitative diet history, assessed to be the most representative of the previous 20 years, was obtained from each subject and analyzed for both food groups and nutrients. The combination of a high-fiber and high-vegetable intake was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
85
0
3

Year Published

1988
1988
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 301 publications
(101 citation statements)
references
References 30 publications
13
85
0
3
Order By: Relevance
“…For P-carotene, ascorbic acid, vitamin E and folate there was a significant trend for a protective effect with increasing consumption quintiles, considering both the model including only age and sex and that including all potential confounding factors. The protective effect was generally more evident after multivariate analysis: the estimated RR for the (Newmark et al, 1984;Garland et al, 1985;Sorenson et al, 1988), ascorbic acid (Kune et al, 1987), P-carotene (Benito et al, 1991), folate (Freudenheim et al, 1991;Giovannucci et al, 1993) or vitamin E (Longnecker et al, 1992), but there have been no systematic efforts to allow for the potential effect of one micronutrient on that of others. This is of specific interest, since several of these micronutrients are highly correlated.…”
Section: Resultsmentioning
confidence: 99%
“…For P-carotene, ascorbic acid, vitamin E and folate there was a significant trend for a protective effect with increasing consumption quintiles, considering both the model including only age and sex and that including all potential confounding factors. The protective effect was generally more evident after multivariate analysis: the estimated RR for the (Newmark et al, 1984;Garland et al, 1985;Sorenson et al, 1988), ascorbic acid (Kune et al, 1987), P-carotene (Benito et al, 1991), folate (Freudenheim et al, 1991;Giovannucci et al, 1993) or vitamin E (Longnecker et al, 1992), but there have been no systematic efforts to allow for the potential effect of one micronutrient on that of others. This is of specific interest, since several of these micronutrients are highly correlated.…”
Section: Resultsmentioning
confidence: 99%
“…The daily consumption of 2% fat-milk or skim milk was not associated with colon cancer but 2% fat-milk was found to be significantly protective for rectal cancer. Four case-control studies reported significant protective effects (Kune et al, 1987;Macquart-Moulin et al, 1986;La Vecchia et al, 1988), but not consistently for both sexes or both colon and rectum. The average estimate from casecontrol studies is OR: 0.98 (95% CI: 0.82 -1.05; (Figure 2).…”
Section: Milkmentioning
confidence: 97%
“…Table 1 contains 30 case -control studies that had at least 99 cases and reported on meat intake (Benito et al, 1990;Bidoli et al, 1992;Centonze et al, 1994;Dales et al, 1979;Gerhardsson et al, 1991;Graham et al, 1978;Haenszel et al, 1973Haenszel et al, , 1980Hu et al, 1991;Iscovich et al, 1992;Kampman et al, 1995Kampman et al, , 1999Kato et al, 1990;Kune et al, 1987; La Vecchia (1992) 248 Italy Yes I R þ beef & pork; C-ve Centonze et al (1994) 118 Italy Yes H NS Dales et al (1979) 99 US Blacks -I N S Gerhardsson et al (1991) 559 Sweden Yes H C and R þ meats Graham et al (1978)) 586 USA (NY) -I N S Haenszel et al (1973) 179 Japanese in Hawaii -L CRC þ meat Heanszel et al (1980) 588 Japan --NS Hu et al (1991) 336 China Yes -NS Iscovich et al (1992) 110 Argentina Yes H NS Kampman et al (1995) 312 Netherlands Yes H NS Kampman et al (1999) 1542 USA Multicentre --NS Kato et al (1990) 221 Japan -I N S Kune et al (1987) 715 Australia Yes -C þ beef men, not women R þ lamb women, not men La Vecchia et al (1988) 575 N. Italy Yes -RR 2.0 CRC for meat but 3.0 for pasta þ rice La Vecchia et al (1996) 1326 N. Itlay -H CRC þ (1.6) for red meat Lee et al (1989) 203 Singapore Yes H NS Lyon et al (1988) 246 Utah, USA Yes -NS Macquart-Moulin et al (1986) 399 France Yes I NS Manousos et al (1983) 100 Greece Yes -CRC þ beef and lamb Miller et al (1983) 542 Canada Yes -R þ beef (?) Muscat et al (1994) 511 USA --NS Peters et al (1989) 146 Los Angeles, USA Yes -NS Peters et al (1992) 746 Los Angeles, USA Yes H NS Steinmetz et al (1993)…”
Section: The Case -Control Studiesmentioning
confidence: 99%